The Impact of Knowledge Management on Organizational Performance: A Structural Equation Modeling Study (2020)
This study attempts to investigate the role of knowledge management (KM) in commercial companies. To this end, the literature was reviewed and relevant components were extracted to conceptualize KM and organizational performance, (OP) and the relationship between KM and OP was presented in a theoretical framework. Secondly, to assess the proposed model, a questionnaire was given to 200 participants in five commercial companies, chosen through multi-stage stratified sampling. The data were analyzed using structural equation modeling (SEM) and Lisrel 8.8. The results revealed that the model enjoyed an acceptable degree of fit. The obtained coefficient (0.41) showed a direct impact of KM indices on OP, indicating the significant and positive relationship between KM and OP dimensions such as financial performance, quality of goods and services, staff members’ performance, innovation, and customers’ level of satisfaction.